How personal task management differs across individuals. Issue 88 (April 2016) - Haraty, Mona; McGrenere, Joanna; Tang, Charlotte
Abstract: There has been a wealth of research on how individuals manage their tasks in general. However little to none has investigated whether, how, and why personal task management (PTM) behaviors differ across individuals. To fill this gap, we conducted two empirical studies: a focus group + contextual interviews with 19 participants, and an online survey with 178 respondents. Initially, based on the results of the first study, we were able to summarize the differences and similarities across the individuals by categorizing the participants into three categories: DIYers, make-doers, and adopters. Then, we conducted a survey with a broader population to assess to what extent our previous results would generalize to a broader population. We found that many of the survey respondents did not fit neatly into one of the previous categories; rather, they demonstrated tendencies of varying strength toward adopting, make-doing, and DIYing for their PTM. This was reflected in how they recorded and remembered their tasks, and if/how they maintained task lists. Based on this, we recommend that PTM tools have the capacity to accommodate the varying strengths of those tendencies: they should be personalizable so that people with DIY desire can personalize their tool when they need to and should be relatively effortless to use and integrate well with other systems in use to satisfy make-do tendencies. Highlights: Summarizes individual differences in PTM by grouping people into three groups: DIYers, make-doers, and adopters. Assesses generalizability & extends the understanding of the above categorization. Extends the understanding of the above user categories. Individuals show varying tendencies toward adopting, make-doing, and DIYing in PTM. Offers implications for the design of personalizable PTM tools.